Gel Filtration - Tangen, O; Berman, H. J; Marfey, P (Thrombosis and Haemostasis, 1971)
Hamster platelets have been separated from their plasmatic enviroment by means of gel filtration. This method of separation gave an excellent yield of platelets free of non-adsorbed plasma proteins.Gel filtered platelets (GFP), and platelets washed by repeated centrifugations and resuspensions (CP) were compared to each other and to platelets left undisturbed in their native plasma (PRP). Only slight morphological differences between the three platelet preparations could be detected by phase microscopy. In the concentration range of .28–.71 μM ADP, GFP, resuspended in PPP, showed the same degree of aggregation as did PRP. At lower concentrations of ADP, GFP aggregated to a lesser degree than did PRP. CP exhibited aggregation comparable to PRP only at higher concentrations of ADP (.71–1.42 (μM ADP). GFP also supported clot retraction to the same extent as did PRP.It would appear that gel filtration provides a new, gentle and rapid method for separation, from plasma, of platelets with activity very similar to that of platelets in PRP.